2008
DOI: 10.1080/14756360701504842
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomimetic 2-cyanopyrrolidines as potent selective cathepsin L inhibitors

Abstract: Cathepsins have been found to have important physiological roles. The implication of cathepsin L in various types of cancers is well established. In a search for selective cathepsin L inhibitors as anticancer agents, a series of 2-cyanoprrolidine peptidomimetics, carrying a nitrile group as warhead, were designed. Two series of compounds, one with a benzyl moiety and a second with an isobutyl moiety at P 2 position of the enzyme were synthesized. The synthesized compounds were evaluated for inhibitory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In this context, current efforts are specifically directed to design new suitable cathepsin K inhibitors which could be devoid of these potential side effects (Black and Percival, 2006;Desmarais et al, 2008;Le Gall et al, 2008;Brömme and Lecaille, 2009). Most of the cathepsin L targeted agents which have been developed are a series of different classes of antagonists including small molecule inhibitors with a higher selectivity for cathepsin L (Katunuma et al, 2002a,b;Marquis et al, 2005;Sadaghiani et al, 2007;Myers et al, 2008;Palermo and Joyce, 2008;Yadav et al, 2008;Asaad et al, 2009;Bethel et al, 2009;Long and Chagnovich, 2009;Rebbaa et al, 2009;Kishore Kumar et al, 2010), alternative forms of endogenous inhibitors (Brand et al, 2004;Gianotti et al, 2008), antibodies and antisense oligonucleotides (Krueger et al, 2001;Rousselet et al, 2004;Frade et al, 2008;Long and Chagnovich, 2009) or natural products (Lion et al, 2009;Ogawa et al, 2009). Preclinical studies showed that some of these molecules were effective to inhibit, in vitro, bone matrix digestion at the level of resorption lacuna and to promote bone mineralization, whereas, in vivo, these agents were able to suppress RANKL or M-CSF or TNF-a stimulated bone pit formation and to protect tumor bearing mice from malignant hypercalcemia and to decrease bone metastasis formation (Hill et al, 1994;Katunuma et al, 2002a,b;Brand et al, 2004;Long and Cha-gnovich, 2009).…”
Section: Cathepsin L Inhibitors In the Treatment Of Cancer Related Bomentioning
confidence: 99%
“…In this context, current efforts are specifically directed to design new suitable cathepsin K inhibitors which could be devoid of these potential side effects (Black and Percival, 2006;Desmarais et al, 2008;Le Gall et al, 2008;Brömme and Lecaille, 2009). Most of the cathepsin L targeted agents which have been developed are a series of different classes of antagonists including small molecule inhibitors with a higher selectivity for cathepsin L (Katunuma et al, 2002a,b;Marquis et al, 2005;Sadaghiani et al, 2007;Myers et al, 2008;Palermo and Joyce, 2008;Yadav et al, 2008;Asaad et al, 2009;Bethel et al, 2009;Long and Chagnovich, 2009;Rebbaa et al, 2009;Kishore Kumar et al, 2010), alternative forms of endogenous inhibitors (Brand et al, 2004;Gianotti et al, 2008), antibodies and antisense oligonucleotides (Krueger et al, 2001;Rousselet et al, 2004;Frade et al, 2008;Long and Chagnovich, 2009) or natural products (Lion et al, 2009;Ogawa et al, 2009). Preclinical studies showed that some of these molecules were effective to inhibit, in vitro, bone matrix digestion at the level of resorption lacuna and to promote bone mineralization, whereas, in vivo, these agents were able to suppress RANKL or M-CSF or TNF-a stimulated bone pit formation and to protect tumor bearing mice from malignant hypercalcemia and to decrease bone metastasis formation (Hill et al, 1994;Katunuma et al, 2002a,b;Brand et al, 2004;Long and Cha-gnovich, 2009).…”
Section: Cathepsin L Inhibitors In the Treatment Of Cancer Related Bomentioning
confidence: 99%
“…The initial series of compounds synthesized concentrated on modification of the P1 position, with benzyl ester protection of the C-terminus (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). At this position, the methylene unit of the C-terminal amino acid glycine was increased in length.…”
Section: Chemistrymentioning
confidence: 99%
“…Inhibitors containing electrophilic moieties such as an aldehyde, halomethyl ketone, or epoxide have been shown to be potent cysteine protease inhibitors 6 . Peptidic molecules containing the electrophilic benzyl ester and nitrile moieties have also been reported to be inhibitors of various cathepsins [7][8][9] . For this study, all of the compounds (1-36) prepared are based on a dipeptidyl scaffold.…”
Section: Introductionmentioning
confidence: 99%